2019
DOI: 10.1590/1517-869220192505203673
|View full text |Cite
|
Sign up to set email alerts
|

Talento Motor E Maturação Biológica Em Escolares De Um Colégio Militar

Abstract: RESUMO Introdução A avaliação do desempenho motor em escolares tem sido utilizada na identificação de talentos esportivos. Porém, existem poucos estudos, sobre esta temática, e nenhum no Sistema Colégio Militar do Brasil. Objetivo Avaliar indicadores antropométricos, fisicomotores e maturacionais; investigar a proporção de talentos motores; analisar a relação entre o diagnóstico de talento motor e o estágio maturacional; e comparar o perfil de alunos-atletas e não atletas de um colégio militar. Métodos Fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…The references of included studies were analyzed in order to identify possible information on the theme not verified during the systematic search; however, no additional studies in relation to those previously identified were included. Thus, 13 studies [17][18][19][20][21][22][23][24][25][26][27][28][29] were included in this review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The references of included studies were analyzed in order to identify possible information on the theme not verified during the systematic search; however, no additional studies in relation to those previously identified were included. Thus, 13 studies [17][18][19][20][21][22][23][24][25][26][27][28][29] were included in this review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies with cross-sectional design were part of the present review. Of this total, seven studies were carried out in the southern region of Brazil (Santa Catarina, n = 04; Paraná, n = 03) 19,[21][22][23][24]26,27 , two studies in the southeastern region (São Paulo, n = 01; Minas Gerais, n = 01) 18,29 , two studies in the northeastern region (Alagoas, n = 01; Piauí, n = 01) 25,28 and one study in the northern region (Amazonas) 17 . Additionally, one study 20 was conducted in states included in the southern and southeastern regions of Brazil (Paraná and São Paulo, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Werneck e Coelho (2020) apresentam a seleção de talentos como uma etapa que pode ocorrer ao longo do processo de treinamento do indivíduo e quando realizada por meio de testes, a seleção pode ser feita baseando-se nesses resultados. et al, 1987), ganhando crescente e com enfoques variados dos anos 2000 em diante (BÖHME, 2000(BÖHME, , 2007KISS et al 2004;MASSA et al, 1999;MIRANDA et al 2019;WERNECK et al, 2020). Em investigações internacionais o tema tem grande relevância na ciência do esporte, o que demonstra a necessidade de novas pesquisas, buscando cada vez mais o entendimento do processo de detecção ao treinamento de longo prazo de jovens atletas (ABBOTT; COLLINS, 2004;BAKER;SCHORER, 2012;DIGEL, 2002;HOHMANN;SEIDEL, 2010;HOHMNANN;SEIDEL, 2003;ISSURIN, 2017;JOHNSTON et al, 2018;OPSTOEL et al, 2015;VAEYENS et al, 2008).…”
Section: Lista De Figurasunclassified